Comprehensive RNA-seq Analysis to Evaluate the Pigmentation-Related Genes Involved in Albinism of Cichlid Fish, Aulonocara baenschi - Lee, Sang Yoon; Lee, Hwa Jin (Frontiers in Marine Science, 2020)
The Nkhomo-benga peacock, Aulonocara baenschi is a species inhabiting Lake Malawi and its population has decreased by over 70% over the past 10 years. Since 2018, the species has been included in the IUCN Red list and its status has been set to the critically endangered (CR) level. And the fish is known to have rare but naturally occurring albino strain. Despite that, little has been done to develop its genetic resources such as sequence-based data and expression patterns of genes. Accordingly, this study performed high-throughput sequencing on the caudal fin of the two different-colored A. baenschi in order to identify their pigment-related genes and analyze the expression patterns of the genes on the transcriptome level. Through the Illumina sequencing platform, we obtained 77,035,702 and 88,689,756 reads from the caudal fin of the wild-type and the albino-type, respectively. In addition to that, using de novo assembly and various annotation databases, a total of 141,116 contigs, including 129,369 unigenes were obtained. In the comparative analysis of differentially expressed genes between the wild-type and the albino-type in terms of melanogenesis, the tyrosinase gene family involved in melanin synthesis tended to be less expressed in the albino-type than the wild-type. However, the expression of the critical proteins involved in the pigment synthesis of xanthophore was higher in the albino-type than in the wild-type. In addition, the yellow-orange pigment was more apparently expressed in the caudal fin of the albino-type than of the wild-type. This indicates that the external characteristics of the fish were in accordance with the analysis results on the transcriptome level. The results of this study will be the foundation of research on expression characteristics and gene networking analysis of the pigmentation-related genes of fish.